Feminist revision of gothic romance in the novel «Lady Oracle» by M. Atwood - Yankuta, Hanna V. (Journal of the Belarusian State University. Philology, 2019)
The article reviews the novel «Lady Oracle» by the Canadian writer M. Atwood in order to determine the nature of the revision of Gothic tradition in the postmodern era. For this, the elements of classical Gothic in the novel are revealed. Scientific novelty of the article is in combining research of the genre nature of M. Atwood’s novel with an analysis of the forms of novel interaction with feminist theories. An overview of Gothic genre history is given and a modification of the Gothic heroes, motifs, images and plot devices in the novel «Lady Oracle» is explored. The parody component of the novel and the image of a creative personality that has both comic and tragic features are analyzed. The article states that genre revision in the novel has feminist nature: reinterpretation of Gothic genre gives the writer the opportunity to delineate the social and cultural codes embedded in the Gothic stories and demonstrate their influence on the female consciousness. The results of the work can be used in the further study of women’s literature, both foreign and Belarusian and its assimilation of the classical literature experience.
Keywords: genre; Gothic romance; feminism; revision; parody